2003
DOI: 10.1002/pssa.200306466
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted nickel deposition onto porous silicon

Abstract: As a direct metal patterning method, local electrodeposition of Ni onto porous silicon (PS) is studied. The principle of the method in this research utilizes the photo-excitation of semiconductor, in contrast to the previous studies of laser assisted metal deposition, in which the deposition is enhanced by heating effects or sensitization by laser irradiation. Electrochemical measurements show the different behaviors between PS and planar Si. The current is lower for PS than planar Si. The higher rate of charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In this context, Takahashi et al demonstrated light-assisted control of electrodeposition under constant applied potential for fabricating a CdTe layer on p-type Si ͑100͒. 26 Laser-assisted maskless patterning of metals on p-type porous Si was also reported by Sasano et al [27][28][29] Utilizing the different properties of Pt deposition on p-type Si in the dark and under illumination, we tried to control Pt electrodeposition on p-type Si by illumination control without any potential step. A schematic diagram of the procedure is shown in Fig.…”
Section: C702mentioning
confidence: 93%
“…In this context, Takahashi et al demonstrated light-assisted control of electrodeposition under constant applied potential for fabricating a CdTe layer on p-type Si ͑100͒. 26 Laser-assisted maskless patterning of metals on p-type porous Si was also reported by Sasano et al [27][28][29] Utilizing the different properties of Pt deposition on p-type Si in the dark and under illumination, we tried to control Pt electrodeposition on p-type Si by illumination control without any potential step. A schematic diagram of the procedure is shown in Fig.…”
Section: C702mentioning
confidence: 93%
“…The use of the laser chemical metal deposition (LCMD) process is considered to be the most suitable process for industrial application. The method can certainly make the process simpler, as the nitride ablation and seed layer formation can be performed in a single step [ 43 , 44 ]. N. Wehkamp et al at Fraunhofer ISE have worked on such type of laser chemical metal deposition methods, and reported an efficiency of 17.9% by forming a 40 μm wide line for solar cell fabricated on p-type CZ silicon substrate [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus this is a promising method which enables maskless patterning of the silicon substrate. Local deposition of Ni onto porous silicon by photo-excitation of the silicon substrate, which is a method for direct metal patterning, has also been studied [ 106 ]. On the spots which are illuminated by the laser beam Ni deposition preferentially takes place due to photo-induced electrons in the conduction band which contribute to the reduction of Ni ions.…”
Section: Filling Of Porous Siliconmentioning
confidence: 99%